VLFBERHT swords: Origin, material, and manufacture - Petri, Ingo (History compass, 2019)
VLFBERHT or ULFBERHT is the most frequent inscription on Viking Age sword blades. The majority of these swords have been found in Scandinavia, much less in the Frankish Empire so that it might seem that they have been produced in Scandinavia. But this is most probably a result of different burial customs. The blades were most probably produced in the Frankish Empire and came to Scandinavia as loot or ransom. The signature has been interpreted as the name of the sword smith. But recently, it has been shown that the person behind this name rather was an overseer over the sword production who had position in ecclesiastical or monastic hierarchy. The reverse side of the blades show geometrical marks. These may have developed from the Pagan serpent or worm symbolism connected to swords. The patterns may have survived into Christian times, but with a changed symbolic meaning. It has always been tried to distinguish between original VLFBERHT blades and imitations or falsifications. Recently, metallographic analyses have shown a correlation between special inscription variants and different methods of manufacture.